2018
DOI: 10.1016/j.scitotenv.2018.06.311
|View full text |Cite
|
Sign up to set email alerts
|

Surface and passive/active air mould sampling: A testing exercise in a North London housing estate

Abstract: Despite indoor mould being one of the most common problems in residential properties in the UK, there are not any widely accepted methodologies for its measurement. This paper focusses on this problem of measurement and reports on the findings from a rigorous testing scheme carried out to quantify air and surface mould concentrations and particle counts within 71 rooms from 64 properties in North London, some with and some without visible mould. The aim was to investigate the potential of passive and active ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…The NAHA activity values (known also as Mycometer values) (Table 2) show that all rooms tested in this study had very low airborne mould concentrations. According to the benchmarks recently developed for the UK building stock and for the same testing protocol as the one used here, NAHA activity values above 1700 RFU could be indicative of mould growth and therefore require further investigation of the space for a mould source [26]. While left unmeasured, the visual evidence suggests that basement should exhibit much higher airborne mould concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NAHA activity values (known also as Mycometer values) (Table 2) show that all rooms tested in this study had very low airborne mould concentrations. According to the benchmarks recently developed for the UK building stock and for the same testing protocol as the one used here, NAHA activity values above 1700 RFU could be indicative of mould growth and therefore require further investigation of the space for a mould source [26]. While left unmeasured, the visual evidence suggests that basement should exhibit much higher airborne mould concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…settled dust on surfaces. Active sampling, on the other hand, uses active mixing of the air in the room to be tested-it will suspend settled dust so its mould activity can be characterised, and has previously been shown to be strongly correlated to the presence of visible mould and other moisture induced problems within the space [11]. In this study, an active air sampling strategy was adopted for its ability to rule out the impact of the prior disturbance (or lack of it) within the space on the readings [2628].…”
Section: Description Of Tested Rooms and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Within this framework, this study aims to establish normal background levels of mould in order to improve the decision-making process as to when a given indoor environment may be in need for remediation by identifying the ranges common to normal, non-water-damaged buildings without visible mould To this end, a testing protocol previously reported by Aktas et al [11,12] was used, which showed that surface and air sampling should be combined to identify local mould problems, and that an active (aggressive or activated) air sampling strategy, i.e. sampling actively mixed air, better represents indoor mould concentrations than a passive sampling approach, i.e.…”
Section: Introductionmentioning
confidence: 99%